Environmental Impact Assessment of FDM-Fabricated Ankle Foot Orthosis Device Using Thermoplastic Materials - Ülkir, Osman; Kuncan, Melih (Springer, 2025)
Sustainability in biomedical applications aims to balance the demands of present and future generations by improving quality of life and minimizing environmental impacts. Fused deposition modeling (FDM), a form of additive manufacturing (AM), has surfaced as an effective approach to promoting sustainability in production. However, there is a lack of comparative studies focusing on the environmental impact assessment of commonly used biocompatible filament materials. This study evaluates the environmental impacts of FDM-fabricated ankle foot orthosis (AFO) using life cycle assessment (LCA) methodology. Biocompatible thermoplastic materials, including polylactic acid (PLA), thermoplastic polyurethane (TPU), polyethylene terephthalate glycol (PETG), and polyether ether ketone (PEEK), were analyzed for their life cycle impacts across three stages: raw material extraction, manufacturing, and recycling. The AFO parts were fabricated with dimensions of 250 mm height and 100 mm foot length using a Creality K1C printer operating at speeds up to 600 mm/s. Material consumption ranged from 109.35 g (TPU) to 115.47 g (PEEK), while manufacturing energy consumption varied between 2.45 kWh (PLA) and 3.11 kWh (PEEK). Energy consumption during recycling ranged from 3.27 kWh for PLA to 4.28 kWh for PEEK. Environmental impacts were identified using mid-point and end-point indicators, such as fossil depletion, human toxicity, and other parameters. The results revealed that PLA is the most environmentally friendly material, showing the lowest impacts across most indicators and costing only $2.52 per part. In contrast, PEEK revealed the highest environmental burden and cost ($46.19 per part), making it the least sustainable material. This research highlights the importance of LCA in promoting sustainability in AM, providing valuable insights to stakeholders in material selection for biomedical applications. © 2025 Elsevier B.V., All rights reserved.
Keywords: Ankle Foot Orthoses; Energy Consumption; Fused Deposition Modeling; Life Cycle Assessment; Sustainability; Artificial Life; Biocompatibility; Biological Materials; Costs; Environmental Impact Assessments; Fabrication; Industrial Research; Life Cycle; Life Cycle Assessment; Medical Applications; Orthotics; Plastic Bottles; Plastic Recycling; Thermoplastics; Ankle Foot Orthose; Biomedical Applications; Deposition Modeling; Effective Approaches; Energy-consumption; Future Generations; Impact Assessments; Quality Of Life; Thermoplastic Materials; Thermoplastic Polyurethanes; Energy Utilization; Sustainable Development